The Renewed Grace on the Sponsor of the Mother, Sheikh Hassan bin Ammar bin Ali, Abi Al-Ikhlas Al-Masry Al-Sharnabili (d.: 1069 AH) - Study and Verification - - Ismail , Ahmed; Younes, Abdul Mohsen (Islamic Sciences Journal, 2023)
ABSTRACT This research deals with the verification of an important manuscript in Hanafi jurisprudence called: (The Renewed Blessing on the Spouse of the Mother) by Sheikh Al-Allama Hassan bin Ammar bin Ali Abu Al-Ikhlas Al-Masry Al-Sharnabili, with which the Sheikh answered an important issue he was asked about, and its image: What do you say as long as you please in a woman who borrowed money from her son, and her guarantor with her permission is a foreigner, then the son wanted to lock up his mother’s guarantor, Is the son allowed to do so? or how is the situation? The Sheikh replied: He does not have the right to imprison him. As it is necessary for his imprisonment to imprison the mother, and that it is not permissible, and he said: I have answered it jurisprudentialy, and that is because I did not see a text from our imams in this case, except that they said: The guarantor is withholding what he has committed to the bail contract, and if necessary, the principal is required, and if he is imprisoned, this is how they were released. The rule is general, and any general rule should be specified. This message, despite its small size, deserves attention and care for most of its usefulness; and because it revolves around an important issue, few scholars have been exposed to it, as that Sheikh mentioned at the beginning of the manuscript.